Chemical Vapour Deposition of MWCNT on Silica Coated Fe3O4 and Use of Response Surface Methodology for Optimizing the Extraction of Organophosphorus Pesticides from Water - Veronica W. O. Wanjeri; Sefater Gbashi; Jane C. Ngila; Patrick Njobeh; Messai A. Mamo; Patrick G. Ndungu (International Journal of Analytical Chemistry)
Multiwalled carbon nanotube (MWCNT) was fixed onto the surface of a magnetic silica (Fe3O4@SiO2) substrate via chemical vapour deposition (CVD). Acetylene gas was used as the carbon source and cobalt oxide as the catalyst. The chemical and physical characteristics of the materials were investigated by transmission electron microscopy (TEM), Raman spectroscopy (RS), scanning electron microscopy (SEM), energy-dispersive spectroscopy (EDS), X-ray diffraction (XRD), and nitrogen adsorption/desorption isotherm. The synthesized Fe3O4@SiO2-MWCNT nanocomposite was used as a magnetic solid phase extraction (MSPE) adsorbent for the preconcentration of organophosphorus pesticides (OPPs), specifically, azinphos methyl, chlorpyrifos, parathion, and malathion. The factors influencing the extraction efficiency such as pH, contact time, and adsorbent dosage were investigated and optimized by response surface methodology (RSM) and desirability function. Linear response was obtained in the concentration range of 10–200 μg/L for the analytes with determination coefficients ranging between 0.9955 and 0.9977. The limits of detection (LODs) and quantification (LOQs) were in the range of 0.004-0.150 μg/L and 0.013-0.499 μg/L, respectively. Fe3O4@SiO2-MWCNT was applied in the extraction and subsequent determination of OPPs in water samples from Vaal River and Vaal Dam with recoveries ranging from 84.0 to 101.4% (RSDs = 3.8–9.6%, n = 3) in Vaal River and 86.2 to 93.8% (RSDs = 2.9–10.4%, n = 3) in Vaal Dam. The obtained results showed that the newly synthesized Fe3O4@SiO2-MWCNT nanocomposite can be an efficient adsorbent with good potential for the preconcentration and extraction of selected OPPs from aqueous media.